Understanding electrical and chemical transmission in the brain - Borroto-Escuela, Dasiel O.; Gonzalez-Cristo, Emmanuell; Ochoa-Torres, Verty; Serra-Rojas, Emilio M.; Ambrogini, Patrizia; Arroyo-García, Luis E.; Fuxe, Kjell (Frontiers in Cellular Neuroscience, 2024)
The histochemical Falck-Hillarp method for the localization of dopamine (DA), noradrenaline (NA) and serotonin in the central nervous system (CNS) of rodents was introduced in the 1960s. It supported the existence of chemical neurotransmission in the CNS. The monoamine neurons in the lower brain stem formed monosynaptic ascending systems to the telencephalon and diencephalon and monoamine descending systems to the entire spinal cord. The monoamines were early on suggested to operate via Integration of Chemical and electrical transmission in the brain 2 synaptic chemical transmission in the CNS. This chemical transmission reduced the impact of electrical transmission. In 1969 and the 1970s indications were obtained that important modes of chemical monoamine communication in the CNS also took place through the extra-synaptic fluid, the extracellular fluid, and long-distance communication in the cerebrospinal fluid involving diffusion and flow of transmitters like DA, NA and serotonin. In 1986, this type of transmission was named volume transmission (VT) by Agnati and Fuxe and their colleagues, also characterized by transmitter varicosity and receptor mismatches. The short and long-distance VT pathways were characterized by volume fraction, tortuosity and clearance. Electrical transmission also exists in the mammalian CNS, but chemical transmission is in dominance. One electrical mode is represented by electrical synapses formed by gap junctions which represent low resistant passages between nerve cells. It allows for a more rapid passage of action potentials between nerve cells compared to chemical transmission. The second mode is based on the ability of synaptic currents to generate electrical fields to modulate chemical transmission. One aim is to understand how chemical transmission can be integrated with electrical transmission and how putative (aquaporin water channel, dopamine D2R and adenosine A2AR) complexes in astrocytes can significantly participate in the clearance of waste products from the glymphatic system. VT may also help accomplish the operation of the acupuncture meridians essential for Chinese medicine in view of the indicated existence of extracellular VT pathways.